EVALUATION OF THE USE OF THE DRUG IN PATIENTS ACUTE RESPIRATORY TRACT INFECTION (ARI) NON PNEUMONIA AT PUSKESMAS SIGUMPAR - Sihombing, Yanna Rotua; Romauli Anna teresia Marbun; Friska Novita Pasaribu; Novidawati Br Situmorang (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Acute Respiratory Infection (ARI) is one of the main causes of patient visits to health centers (40%-60%) and hospitals (15%-30%). In Indonesia the level of use of antibiotics is still quite high. The unwise use of antibiotics and the incorrect application of standard precautions in health care facilities an lead to the occurrence of resistane. This study aims to determine the evaluation of drug use in non-pneumonia Aucute Respiratory Infection (ARI) patients at the Sigumpar Health Center. This Type of research is an observational study with a descriptive design and data taken retrospectively. The total sample of 101 medical records was taken by purposive sampling technique. The patients who often suffer from non-pneumonia acute respiratory infections at the Sigumpar Health Center occur in the age group of 6-11 years, namely children by 20,79%. Based on the results of this study, the most widely used drugs were analgesic-antipyretic (69.30%), antihistamine (65.34%), vitamins (62.37%), mucolytics (48.51%), expectorants (32.67%), antibiotics (27.72%) and corticosteroids (23.76%). The use antibiotics for non-pneumonia ARI patients at the Sigumpar Health Center was 27,72% so that it was categorized as not in accordance with the provisions of the Inonesian Ministry of Health in 2017 that the use of antibiotics in non-pneumonia ARI patients was ? 20%.